2015
DOI: 10.1093/jhps/hnv072
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion of the direct head of rectus femoris following arthroscopic subspine impingement resection: a case report

Abstract: Arthroscopic resection of the anterior inferior iliac spine (AIIS) for subspine impingement has become a relatively common procedure. The AIIS is the origin of the direct head of rectus femoris (dhRF). Previous studies have reported that removal of the contributing portion of the AIIS causing impingement is unlikely to weaken the attachment of the dhRF. The purpose of this article is to report a case of avulsion of the dhRF, following revision hip arthroscopy for the treatment of subspine impingement. A 23-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…They usually are a result of forceful kicking with abrupt arrest, causing avulsion of the rectus femoris at the anterior infericor iliac spine. Other described mechanisms consist of sudden deceleration in running sports and hip hyperextension with a flexed knee [ 7 ]. It has been postulated that patients who underwent hip arthroscopy for FAI are prone to these injuries more than individuals with no previous surgery, lowering the threshold for injury [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They usually are a result of forceful kicking with abrupt arrest, causing avulsion of the rectus femoris at the anterior infericor iliac spine. Other described mechanisms consist of sudden deceleration in running sports and hip hyperextension with a flexed knee [ 7 ]. It has been postulated that patients who underwent hip arthroscopy for FAI are prone to these injuries more than individuals with no previous surgery, lowering the threshold for injury [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This report discusses the case of a 21-year-old male patient who was found to have an anterior inferior iliac spine avulsion fracture 11 months post hip arthroscopy for femoroacetabular impingement. According to a review of literature on hip arthroscopy complications, few similar cases were reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the heterotopic ossification lesion was large in size, and pathomorphology and treatment were in accordance with those in Type III. Arthroscopic resection of the AIIS for subspine impingement is thought of as a relatively safe procedure, although a case of avulsion of the rectus femoris direct head following revision hip arthroscopy for the treatment of subspine impingement in a 23-year-old professional footballer was reported recently [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 18 During the focal subspinal decompression, however, over-resection of the subspinal area should be avoided, because the rectus femoris could be detached from its origin, leading to a potential hip flexion deficit. 19 To minimize this risk, we carefully conduct a dynamic impingement test during hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%